HEALTH AND SOCIAL CARE COMMISSIONING - Kaur, Manjot (International Journal of Psychosocial Rehabilitation, 2021)
The 2019 coronavirus pandemic (COVID-19) is a result of the severe acute coronavirus syndrome in the United Kingdom (COVID-19) (SARS-CoV-2). The virus made its way into the area around the end of January of the next year. As of 3 February 2021, there were 3,871,825 confirmed cases and 109,335 confirmed deaths in the world's fourth-highest mortality rate for 100 000 persons (Holton, 2020). By the 22nd of January 2021, the COVID-19 certificate had recorded the deaths of 112,972 people throughout the four countries. Hospitals, independent governments, and parliaments, as well as the smaller private sector and volunteer facilities, are all devolved subjects in the United Kingdom (UK).